2021
DOI: 10.1038/s41598-021-85022-x
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6-inhibiting drugs and risk of fall injuries after newly initiated antidepressant and antipsychotic therapy in a Swedish, register-based case-crossover study

Abstract: Drug-drug interactions have been shown to affect the risk of fall injuries when opioids are used concomitantly with drugs inhibiting the cytochrome P450 2D6 (CYP2D6) enzyme in a previous pharmacoepidemiological study. The aim of this study was to determine whether CYP2D6-inhibiting drugs reinforce the risk of fall injuries when used concomitantly with antidepressants or antipsychotics. We identified all 252,704 adults with a first fall injury leading to hospitalisation from the National Patient Register in Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The large number of concurrent medications in SSRI users may double the fall-related injury risk by the potential drug–drug interactions with the SSRIs. The results from previous case crossover studies relate to the results of this study by reporting the increased risk of fall-related injuries in SSRI users with concomitant use of CYP2D6-inhibiting drugs and the non-significant association with TCA users in the older population (70 years or older) [ 10 ]. The effects of the number of concurrent medications on SSRI users compared to TCA users may be a plausible explanation for the previous observational reporting of the greater risk of falls or fractures for TCA users.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The large number of concurrent medications in SSRI users may double the fall-related injury risk by the potential drug–drug interactions with the SSRIs. The results from previous case crossover studies relate to the results of this study by reporting the increased risk of fall-related injuries in SSRI users with concomitant use of CYP2D6-inhibiting drugs and the non-significant association with TCA users in the older population (70 years or older) [ 10 ]. The effects of the number of concurrent medications on SSRI users compared to TCA users may be a plausible explanation for the previous observational reporting of the greater risk of falls or fractures for TCA users.…”
Section: Discussionmentioning
confidence: 61%
“…While antidepressant dose and drug choice were investigated as contributing factors to the risks of each antidepressant subclass, the drug–drug interaction in older adults is another aspect that should be considered. A recent case crossover study of SSRI and SNRI users with the concomitant use of CYP2D6-inhibiting drugs reported a significant risk of fall-related injuries in adults aged 70 years or older [ 10 ]. In contrast, the risk of fall-related injuries was not elevated in TCA users with the concomitant use of CYP2D6-inhibiting drugs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, drug‒drug interactions can result in toxicity that can lead to hospital admissions [ 29 ]. A recent case crossover study showed that concomitant use of antidepressants, many of which are CYP2D6 substrates, with CYP2D6-inhibiting drugs was associated with an increased risk of fall injuries [ 30 ]. Furthermore, several studies evaluating polypharmacy and drug‒drug interactions have shown that optimizing treatment plans can reduce healthcare and medication costs [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the unintentional poisoning events are acute (86.8%) while a much smaller proportion seem to be due to chronic exposure (9.55%) [ 10 ]. Regarding the vulnerability to adverse drug events due to age-related changes, multimorbidity, or polypharmacy, older adults may be more vulnerable (e.g., a high risk of fall injuries and injurious road traffic crashes) at the start of a newly prescribed drug [ 11 , 12 ], and it is hence important to pay more attention to the short-term effects of medications.…”
Section: Introductionmentioning
confidence: 99%